Potensi Bubuk Cengkeh dalam Menekan Perkembangan Jamur pada Benih Kacang Tanah Secara In-Vitro - Siahaya, Anna; Amanupunyo, Handry R D; Tuhumury, Gratiana N C (Universitas Pattimura, 2023)
This study aims to find the type of clove leaf powder and dosage that is effective for suppressing the development of the fungusAspergillus sp. on peanuts. This study used powdered clove leaves of tuni, raja, and forest obtained from Waai Village, Salahutu District. A completely random design was used in this study, with 12 treatment combinations and 3 replications. The results showed that the development of fungiAspergillus flavus inhibited at a dose of 1 g/100 mL PDA as evidenced by an inhibition of 91% by tuni clove leaf powder as well as being able to suppress aflatoxin production from the fungus. These results were statistically shown in the following parameters, namely: colony diameter, inhibition, and the formation of aflatoxin in the treatment.